Pengaruh Gaya Belajar dan Self-confidence Siswa Terhadap Hasil Belajar Siswa pada Mata Pelajaran Geografi di SMA Negeri 1 Sawan - Sembiring, Mika Kori Lahaya Br; Christawan, Putu Indra; Suryana, I Gede Eka (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study aims to analyze the influence of learning style and confidence on student learning outcomes in Geography subjects in grades XI-B SMA Negeri 1 Sawan. This study uses a quantitative approach with an ex post facto method. The subjects in this study were 33 students in grades XI-B. The research instruments are in the form of questionnaires and value documentation. The results of the study show that students' learning styles and confidence have a positive and significant influence on geography learning outcomes. Learning style has a positive and significant influence on learning outcomes with a significance value of 0.000 and a regression coefficient of 0.346. Similarly, student confidence has a positive and significant influence on learning outcomes with a significance value of 0.000 and a regression coefficient of 0.253. The amount of contribution of the two independent variables to learning outcomes is shown by the determination of 62.7%. The findings of this study include learning styles and confidence that affect student learning outcomes at SMA Negeri 1 Sawan. Students at SMA Negeri 1 Sawan mostly have an audiotorial learning style and confidence that is in the middle to high category, but until now students still do not understand learning style and confidence, so that student learning outcomes are still relatively low with 48.48% of students still obtaining low learning outcomes. It is important for students to understand their learning style and confidence so that students can more easily understand learning, especially in geography learning.